HUMANITY IN THE AGE OF AUTOMATION: THE SOCIAL-PSYCHOLOGICAL IMPLICATIONS OF THE LOSS OF TRADITIONAL JOBS - Marlina, Nina Siti (Advances In Social Humanities Research, 2023)
The development of automation technology and artificial intelligence has created a major transformation in the world of work, including shifting various types of traditional work that have been the support of human life and social identity. This research aims to identify the socio-psychological impact of traditional job loss, understand how individuals rebuild the meaning of life, as well as offer adaptation strategies based on a humanistic approach. The method used is a qualitative approach with a phenomenological design, equipped with a descriptive quantitative survey. Interviews were conducted with 15 informants from sectors affected by automation in three major cities, and questionnaires were distributed to 100 respondents to strengthen the findings. The results of the study show that job loss triggers a variety of emotional responses such as anxiety, loss of motivation, mild depression, and identity crises. The depressive phase lasts between 3–6 months before individuals begin to establish new meaning through spirituality, community, or informal economic activities. Factors that affect the success of adaptation include age, educational background, and social support. This study concludes that the humanitarian impact of automation requires more attention in employment, education, and social protection policies. An adaptation strategy is needed that combines psychological mentoring, digital training, and community strengthening as part of an inclusive and equitable social transformation.